Rattan Spiny Morphology And Litter Collecting Structures In Association With Ant Colonies - Kunpeng, Liu (2019)
Rattan is a common palm in Malaysian forests but rarely known except for their economic values in furniture or matting products. Many rattan species possess a great number of spines arrangement in various patterns. However, few studies have looked into the different aspects of those spiny structures and their unique functions. This study focused on rattan spine structures in five different species which are common in the northern part of Peninsular Malaysia; they are Daemonorops lewisiana, Daemonorops geniculata, Calamus castaneus, Plectomia griffithii and Korthalsia scortechinii. Spine length, width, inclination, density, and strength were measured, and comparison from every aspect was taken to find out which rattan species possess the greatest defensive abilities to protect themselves. The leaf hairs characteristics on leaflets of D. geniculata, D. lewisiana, and C. castaneus were also measured. The results showed that none of the species has an outstanding defensive weapon since every species have their advantages. D. geniculata has the longest spines; D. lewisiana has the strongest spines; C. castaneus has the greatest the number in density and P. griffithii’s down-pointing spines may effectively deter small climbing mammals. K. scortechinii has nothing special in its spiny structures but was still well defended by ant partners colonizing their ocrea structures. Therefore, a rattan plant may rely on multiple defensive strategies and spiny structures only contribute part of its defensive role. During the study, many ant colonies were found on certain species of rattan plants.